2021
DOI: 10.1002/hpm.3379
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with knowledge and practice of optimal breastfeeding among mothers in Dubai

Abstract: Although breastfeeding has been the primary source of nutrition for infants, many women do not choose to practise breastfeeding due to lack of knowledge, inability to do so or personal choices. This study aimed at determining the breastfeeding practices and examining the sociodemographic factors associated with optimal breastfeeding among mothers attending child welfare clinic at Dubai Health Authority. A structured questionnaire was designed consisting of sociodemographic data, knowledge, attitude and practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
(42 reference statements)
0
3
0
1
Order By: Relevance
“…These results agreed with Neela et al [18] , and Pereira et al, [19] who investigated the association of cleft lip and palate in people born to consanguineous parents and found that a minority had a family history of cleft lip or palate which is consistent within his study about associated malformations of orofacial clefts who revealed that less than quarter of studied children has a positive family history of cleft lip or palate without associated malformations. On the other hand, the results of the current study disagreed with Omar et al [20] in a study about the influence of consanguinity on familial clefting among Palestinians who found that more than half of children with cleft palate had a positive family ~ 5 ~ history of clefting.…”
Section: Discussioncontrasting
confidence: 99%
“…These results agreed with Neela et al [18] , and Pereira et al, [19] who investigated the association of cleft lip and palate in people born to consanguineous parents and found that a minority had a family history of cleft lip or palate which is consistent within his study about associated malformations of orofacial clefts who revealed that less than quarter of studied children has a positive family history of cleft lip or palate without associated malformations. On the other hand, the results of the current study disagreed with Omar et al [20] in a study about the influence of consanguinity on familial clefting among Palestinians who found that more than half of children with cleft palate had a positive family ~ 5 ~ history of clefting.…”
Section: Discussioncontrasting
confidence: 99%
“…Studies reported longer duration of breastfeeding in Arab countries. 13,22,26 The key identified reasons for discontinuing breastfeeding were not enough breast milk and that the child was still hungry after breastfeeding. Perceived insufficient milk supply is the most common reason for women to stop breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10] Although Muslim Arab mothers are motivated to breastfeed from religious teaching, they often lack the knowledge of exclusive breastfeeding practices or hold cultural myths that hinder successful breastfeeding. [11][12][13] For example, prelacteal feeding (eg, water, sugar water, salt solution, crushed dates, artificial milk, animal milk, yogurt, gripe water, herbal tea, and black tea) is given for the first three days after delivery based on the belief that it cleanses the bowels of the newborn until the mother produces "white" milk. 12,14,15 Prelacteal feeding interferes with exclusive breastfeeding and makes breastfeeding more difficult to establish.…”
Section: Introductionmentioning
confidence: 99%
“…Other than personal choices, many mothers don’t practice BF due to a lack of knowledge or incapability to do so [ 37 ]. Inability to express human milk proves to be one of the major factors affecting BF in early postnatal period [ 38 ].…”
Section: Discussionmentioning
confidence: 99%